Strangers Meet in Virtual Libraries. - Magee, C. Max (Poets & Writers)
Features LibraryThing, a book cataloguing Web site developed by computer programmer Tim Spalding in the U.S. Utilization of the various book databases on the Web; Purchase of a stake in the site by Abebooks.com; Potentiality of the site as an online forum.